(untitled) (Journal of Economic Research & Business Administration, 2015)
Formation of the organization of innovative activity in the Republic of Kazakhstan is one of the leaders in the development of the country itself. In Kazakhstan , the last few years, interest in innovation has grown very significantly – even at the level of governments have taken measures to stimulate innovation. Innovation in Kazakhstan has not yet received that theoretical and practical level , which would help to bridge the technological gap , change in the nature and volume of production in all sectors of the economy . Kazakhstan to enter on terms equal partner in the world community , it is necessary to define a circle macrotechnologies by which it can become internationally competitive high-tech products . In modern conditions, a significant impetus to innovation processes can give the development of integration , cooperation ties at the national and international level . Thus, the inherent theoretical and methodological foundations of innovation require further development and generalization. In this regard, the present article describes the features of advanced technology , and in this paper we consider the experience of foreign countries to innovate in practice.